A novel phosphodiesterase of the GdpP family modulates cyclic di-AMP levels in response to cell membrane stress in daptomycin-resistant enterococci (2020)
Substitutions in the LiaFSR membrane stress pathway are frequently associated with the emergence of antimicrobial peptide resistance in both Enterococcus faecalis and Enterococcus faecium Cyclic di-AMP (c-di-AMP) is an important signal molecule that affects many aspects of bacterial physiology, including stress responses. We have previously identified a mutation in a gene (designated yybT) in E. faecalis that was associated with the development of daptomycin resistance, resulting in a change at position 440 (yybTI440S) in the predicted protein. Here, we show that intracellular c-di-AMP signaling is present in enterococci, and on the basis of in vitro physicochemical characterization, we show that E. faecalisyybT encodes a cyclic dinucleotide phosphodiesterase of the GdpP family that exhibits specific activity toward c-di-AMP by hydrolyzing it to 5'pApA. The E. faecalis GdpPI440S substitution reduces c-di-AMP phosphodiesterase activity more than 11-fold, leading to further increases in c-di-AMP levels. Additionally, deletions of liaR (encoding the response regulator of the LiaFSR system) that lead to daptomycin hypersusceptibility in both E. faecalis and E. faecium also resulted in increased c-di-AMP levels, suggesting that changes in the LiaFSR stress response pathway are linked to broader physiological changes. Taken together, our data show that modulation of c-di-AMP pools is strongly associated with antibiotic-induced cell membrane stress responses via changes in GdpP activity or signaling through the LiaFSR system.